Managing Conflict Through: Cross-Border Cooperation: A Study at the Indonesia-Timor Leste Border - Sandy Nur Ikfal Raharjo (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2016)
Since the separation of Timor Leste from Indonesia in 2002, disputes over the border area have existed and have occasionally escalated to be communal conflicts. Due to the involvement of people to people relations, government to government negotiation is not enough to resolve these conflicts. Hence, both countries established cross-border cooperation as an alternative. This research analyzed the role of cross-border cooperation in managing communal conflicts in the border area between the Timor Tengah Utara District of Indonesia and the Oecussi District of Timor Leste. The research was conducted in a qualitative approach, while the data was collected by interview, observation, and literature review. This study showed that crossborder cooperation played a significant role in managing the conflict by reducing violence, building and maintaining social relations, as well as improving the economic development of the local people.